Analysis of Bank Health Level Using RGEC Methods (Risk, Governance, Earning, Capital) on Bank Negara Indonesia (Persero) Tbk Period 2020 - 2022 - Reza Rahmawati; Esty Apridasari; Era Yudistira; Primadatu Deswara (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study was conducted with the aim of determining the health level of PT Bank Negara Indonesia (Persero) Tbk during the period 2020 - 2022 based on composite ratings using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). This type of research is descriptive quantitative using secondary data sources in the form of BNI's annual financial statements. The results of this study indicate that during the period 2020 - 2022, Bank BNI experienced a significant improvement in performance. NPL decreased from 4.3% to 2.8%, LDR value stabilized in the healthy range, ROA increased from 0.5% to 2.5%, NIM ratio increased from 4.5% to 4.8% and CAR ratio remained above 19%, besides that the GCG aspect shows a positive trend with an increase in CGPI scores and strengthening internal governance. The final composite rating of BNI bank based on the average score of the four components is 1.80, which is in the PK-2 (Healthy) category. This indicates that BNI bank has a good ability to manage risk, implement corporate governance, maintain profitability and maintain adequate capital